Cone beam computed tomography evaluation of midpalatal suture maturation in adults. Issue 12 (December 2017) - Angelieri, F.; Franchi, L.; Cevidanes, L.H.S.; Gonçalves, J.R.; Nieri, M.; Wolford, L.M.; McNamara, J.A.
Abstract: The aim of this study was to evaluate midpalatal suture maturation in adults, as observed in cone beam computed tomography (CBCT) images. CBCT scans from 78 subjects (64 female and 14 male, age range from 18 to 66 years) were evaluated. Midpalatal suture maturation was verified on the central cross-sectional axial slice in the superior–inferior dimension of the palate, using methods validated previously. Intra-examiner agreement was analyzed by weighted kappa test. Multinomial logistic regression was used to test whether sex and chronological age (adults <30 years or ≥30 years) could be used as a predictor for the maturational stages of the midpalatal suture. The majority of the adults presented a fused midpalatal suture in the palatine (stage D) and/or maxillary bones (stage E). However, the midpalatal suture was not fused in 12% of the subjects. Sex and chronological age were not significant predictors of the maturational stages of the midpalatal suture. The individual assessment of midpalatal suture maturation by way of CBCT images may provide reliable information critical to making the clinical decision between rapid maxillary expansion and surgically assisted rapid maxillary expansion for the treatment of maxillary atresia in adults.